2020
DOI: 10.13106/jafeb.2020.vol7.no8.635
|View full text |Cite
|
Sign up to set email alerts
|

Disputes in Managing Projects: A Case Study of Construction Industry in Vietnam

Abstract: The construction industry in developing countries like Vietnam, which incorporates small and medium construction enterprises, is typically more prone to disputes and contract dispute-related lawsuits. A dispute may occur at any time in the life cycle of the project. It is sometimes solved with the intermediation of a lawyer or directly by stakeholders. Understanding the causes of disputes in a construction project not only improves the efficiency of a company but also increases the success of projects. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In recent years, Vietnam is become one of the emerging markets with moderate economic growth (Ha & Ngoc, 2020;Vo et al, 2020;Nguyen & Ngoc, 2020;. This growth is due to the success of the accounting and auditing activities in companies, especially derivative accounting tools for risk management.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Vietnam is become one of the emerging markets with moderate economic growth (Ha & Ngoc, 2020;Vo et al, 2020;Nguyen & Ngoc, 2020;. This growth is due to the success of the accounting and auditing activities in companies, especially derivative accounting tools for risk management.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the Vietnamese construction industry identified several factors, including KM and project performance [81]. Several authors identified sourcing expertise, technology utilization for information and knowledge sharing [82,83], management effectiveness [84], human resources development [85,86], financial capacity [86,87], teamwork [88], and soft skills [89] as key pillars affecting construction project performance (Table 1). Moreover, in construction project management, previous studies stated that unskilled labor, workmanship, poor design capabilities, and obsolete construction technology impact an organization's ability to manage complex projects in Vietnam [11].…”
Section: A Case Of the Vietnamese Construction Industrymentioning
confidence: 99%
“…They found that capital structure significantly positively affects profitability. Co et al (2021) studied 18 Vietnamese-listed rubber companies (2015-2019), using regression analysis to explore the relationship between profitability and debt-to-equity ratio. They found a positive relationship with overall debt but a negative one with long-term debt.…”
Section: Literature Reviewmentioning
confidence: 99%
“… TANG (Asset Turnover): Measures revenue generation efficiency from assets, computed as Net Sales to Total Assets. This is expected to positively influence business performance (Onaolapo and Kajola, 2010;Co et al, 2021).…”
Section: Research Modelmentioning
confidence: 99%